Wilms tumor associated with Cushing s syndrome - A case report - Madarina Julia, Madarina Julia (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Ectopic ACTH syndrome associated with Wilms tumor is ver